Analysis of the completeness of specific nutritional interventions as an effort to prevent stunting: an observational study - Setianingsih, Triseu; Hussain, Nervana (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Handling stunting through nutritional interventions is classified into two categories: specific nutrition interventions and sensitive nutrition intervention. Specific nutrition interventions referring to causal factors directly related to nutrition, aimed at pregnant women and breastfeeding mothers, are the responsibility of the health sector, contributing 30%. The completeness of specific nutritional interventions for breastfeeding mothers according to standards are more challenging. The purpose of this study is to analyze several factors that influence the completeness of specific nutritional interventions in breastfeeding mothers to create prediction models. Methods: This was a quantitative study with a cross sectional design. The population was all breastfeeding mothers with a total of 193 nursing mothers. Samples of 128 people were taken using a simple random sampling technique. Data analysis using univariate analysis, bivariate analysis with Chi square analysis and Multivariate analysis with logistic regression analysis. Result: In bivariate analysis there were 8 influencing variables. The Mother’s education with p=0.006, Mother’s knowledge with p=0.001, Mother’s Attitudes with p=0.001, Mother’s Job with a p=0.001, Parity with p=0.001, Husband's Support with p=0.001, Health Workers’ Support with p=0.001, Village Officials’ Support with p=0.001. The most influential variable was the health workers’ support variable with OR=20.56. Through multivariate analysis, a predictive model of achieving completeness of specific nutritional interventions is produced so that it can be used as a preventive effort in overcoming these problems. Conclusion: The completeness of specific nutritional interventions for breastfeeding mothers has not been achieved according to the government's target, it is necessary to intervene on the factors that influence it which include mother’s knowledge, mother’s attitude, husband’s support, health workers’ support and village apparatus’ support.Keyword : Stunting, nutritional support, specific intervention